2015
DOI: 10.1007/s00221-015-4317-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity modulates the change in cerebral blood flow following aerobic exercise in chronic stroke

Abstract: The mechanisms supporting functional improvement by aerobic exercise following stroke remain incompletely understood. This study investigated how cycling intensity and aerobic fitness influence cerebral blood flow (CBF) following a single exercise session. Thirteen community-living stroke survivors performed 20 min of semi-recumbent cycling at low and moderate intensities (40-50 and 60-70 % of heart rate reserve, respectively) as determined from an exercise stress test. CBF was quantified by arterial spin labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Gauthier et al (2015) found both positive and inverse correlations between CVR and aerobic fitness in older adults, and this, along with the Robertson et al (2015) study adds to the evidence that aerobic fitness may have complex, regionally varying and age dependent effects on the brain. Although the direction of the correlation in stroke survivors in the thalamus and posterior cingulate cortex contradicts the current results, the current study and those of Robertson et al (2015) and Gauthier et al (2015) further suggest that aerobic fitness may exert localized effects on CBF (Thomas et al, 2013;Chaddock-Heyman et al, 2016). Given that participants in each of these cited studies have differed in age and health status, the fact that consistent findings have not been reported is unsurprising.…”
Section: Vo 2 Peak Cbf and Cvrsupporting
confidence: 56%
See 2 more Smart Citations
“…Gauthier et al (2015) found both positive and inverse correlations between CVR and aerobic fitness in older adults, and this, along with the Robertson et al (2015) study adds to the evidence that aerobic fitness may have complex, regionally varying and age dependent effects on the brain. Although the direction of the correlation in stroke survivors in the thalamus and posterior cingulate cortex contradicts the current results, the current study and those of Robertson et al (2015) and Gauthier et al (2015) further suggest that aerobic fitness may exert localized effects on CBF (Thomas et al, 2013;Chaddock-Heyman et al, 2016). Given that participants in each of these cited studies have differed in age and health status, the fact that consistent findings have not been reported is unsurprising.…”
Section: Vo 2 Peak Cbf and Cvrsupporting
confidence: 56%
“…A study by Robertson et al (2015) in stroke survivors, using single inversion time PCASL, similarly found an inverse correlation between precuneus CBF and aerobic fitness, but a positive correlation between thalamic and posterior cingulate CBF and aerobic fitness. Gauthier et al (2015) found both positive and inverse correlations between CVR and aerobic fitness in older adults, and this, along with the Robertson et al (2015) study adds to the evidence that aerobic fitness may have complex, regionally varying and age dependent effects on the brain.…”
Section: Vo 2 Peak Cbf and Cvrmentioning
confidence: 87%
See 1 more Smart Citation
“…2015) found both positive and inverse correlations between CVR and aerobic fitness in older adults, and this, along with theRobertson et al (2015) study adds to the evidence that aerobic fitness may have complex, regionally varying and age dependent effects on the brain. Although the direction of the correlation in stroke survivors in the thalamus and posterior cingulate cortex contradicts the current results, the current study and those ofRobertson et al (2015) andGauthier et al (2015) further suggest that aerobic fitness may exert localised effects on CBF …”
mentioning
confidence: 62%
“…A study by Robertson et al (2015) in stroke survivors, using single inversion time PCASL, similarly found an inverse correlation between precuneus CBF and aerobic fitness, but a positive correlation between thalamic and posterior cingulate CBF and aerobic fitness. Gauthier et al Thomas et al, 2013).…”
Section: ̇O 2peak Cbf and Cvrmentioning
confidence: 87%